Ekstrakurikuler Drumb Band di MI Salafiyah Kalirandu Pemalang Dalam Pendidikan Karakter Siswa - Anisah, Himatul Fiqriza; Laila Robi’ah Al Adawiyah; Maylinda Islakhulia; Musyarofah Khoirunnisa; Dian Rif’iyati (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2024)
Abstract Character education is the most important to be internalized in children, especially in this millenial era. Drum band extracurricular activities that are mostly liked by students can be an activity to internalize the character of the discipline. The purpose of this research is to explain the character education of students through drum band extracurricular activities at MI Salafiyah Kalirandu Pemalang. The method used by researchers is descriptive field research using a qualitative approach. The results of this study are (a) Character education in extracurricular drum band runs with reference to school work programs, training activities include the formation and development of character values, as well as monitoring and evaluation by the Principal, Coaches, and Trainers. (b) Character value education in this activity includes faith, honesty, discipline, hard work, independence, friendship, and responsibility. (c) The driving factor for this activity is good cooperation between the Principal, presenters, supervising teachers, and parents. The inhibiting factors come from the limitations of school facilities and infrastructure and from the students themselves. Keywords: Drum Band, Extracurricular, Character Education, Student